Discovering the Arctic: Socio-Humanitarian Studies of USSR Academy of Sciences in Northern Regions of Yakutia in 1980s-1991s - A. A. Suleymanov (Научный диалог)
A pioneering attempt in historiography presents a scientific analysis of socio-humanitarian research carried out by employees of the USSR Academy of Sciences in the Arctic regions of Yakutia during 1980-1991. Archival materials identified by the author, as well as data from the scientific literature were used for the preparation of the article. The work carried out allowed us to present a characteristic of the development by scientists of a complex of sociocultural, economic, archaeological, historical and anthropological, linguistic and folklore issues. In this regard, the geography of the research is shown, their key actors and main directions are identified. At the same time, an analysis of the most important provisions developed by the participants of the considered research initiatives was carried out. It was established that in the mentioned period, on the one hand, the research was continued, which had been successfully carried out earlier in the Polar Yakutia, and on the other hand, new research trends were making their way. Their stipulation is proved by the development of scientific knowledge and the changing socio-political situation in the Soviet Union. It is concluded that, as a result, interdisciplinary research has been developed, including the widespread use of the natural science arsenal, as well as a clear shift in the paradigm regarding the assessment of Soviet transformations for the destiny of the indigenous peoples of the North.